Effects of silymarin on methotrexate-induced nephrotoxicity in rats - Dabak, Durrin Ozlem; Kocaman, Nevin (Taylor & Francis Ltd, 2015)
Methotrexate (MTX) is widely used in the treatment of various malignancies and nononcological diseases but its use has been limited by its nephrotoxicity. Silymarin (SLY), a natural flavonoid, has been reported to have antioxidant, anti-inflammatory and anti-apoptotic effects. This study was carried out to determine whether SLY exerts a protective effect against MTX-induced nephrotoxicity. Rats were divided into six groups: Group 1 (saline, i.p., single injection), Group 2 (0.5% carboxymethyl cellulose (CMC), by gavage once daily for five consecutive days), Group 3 (SLY, 300 mg/kg per day, i. p. for five consecutive days), Group 4 (MTX, 20 mg/kg, i.p., single injection), Group 5 (MTX + CMC similarly as groups 2 and 4) and Group 6 (MTX + CMC + SLY similarly as groups 2, 3 and 4). Histopathologic alterations including apoptotic changes of the kidney were evaluated. MTX injection exhibited dilated Bowman's space, inflammatory cell infiltration, glomerular and peritubular vascular congestion and swelling of renal tubular epithelium cells. Apoptotic cell death was also markedly increased in renal tubules after MTX administration. SLY treatment resulted in statistically significant amelioration in the histological alterations and reduced the number of TUNEL-positive cells as compared with the MTX treated rats (p < 0.05). In conclusion, SLY treatment leads to a reduction on MTX-induced renal damage in rats. Since SLY is safe and acceptable for human consumption, further studies to define the exact mechanism of the protecting effect of SLY on MTX-induced nephrotoxicity and the optimum dosage of this compound would be useful.
Keywords: Apoptosis; methotrexate; nephrotoxicity; rat; silymarin